Drogas e sistema socioeduativo: processo formativo em redução de danos para socioeducadores - Calixto, Francisca Graziele Costa (2022)
The use of substances by adolescents who commit an offense in Brazil is part of a context in which a moralizing and criminalizing view of drug use prevails. With this, the objective was to propose a reflective strategy in harm reduction in the Socio-Educational Center of Sobral/CE. As a way of accessing these perceptions more concretely, a training course on drugs and their aspects was facilitated. The course is also configured as a potential technical product that can be replicated in different spaces that act with the application of socio-educational measures. From this, throughout the formative process itself, data were collected to be analyzed within the speech brought by these psychosocial professionals under opinion number: 5,642,482 of the Ethics and Research Committee. 17 socio-educators, 06 women and 11 men, participated during a period of three months. For the analysis of the contents that emerged during the process, content analysis was used via IRaMuTeQ, which resulted in four classes found in the process, which were “Class 1 – The role of the socio-educator in monitoring adolescents and the obstacles of resocialization”, in which the socio-educator discredits the adolescent's social reintegration, mainly due to the environment in which he is inserted. In “Class 2 – The context of substance use in adolescence, inefficiency of public policies and the need to reorganize the socio-educational system”, for him, policies do not reach them and are not guaranteed, so that the view should not be simplistic as some point, but multidetermined. According to Class 3 – The challenges and lack of recognition in the work of the socio-educator who works with adolescents in conflict with the law” puts this group in a power struggle with the system that seeks to protect the adolescent and ends up weakening the work of the socio-educator who feels undervalued. Finally, “Class 4 – Perspectives on the influence of substance use, harm reduction and professional training”, these professionals do not feel able to address the issue of d rugs, much less from the perspective of harm reduction.